Oil Price and Earnings Management: Evidence from Crude Oil and Gas Companies in Indonesian Stock Exchange - Mela, Nanda Fito; Putra, Adhitya Agri (International Journal of Energy Economics and Policy, 2020)
This research is aimed to examine the effect of oil price on earnings management in Indonesia. Research sample consist of 9 crude oil and gas companies listed in Indonesian Stock Exchange for the 2013-2018 period. Earnings management is measured by discretionary accruals. Analysis data uses regression analysis. Result shows that oil price has negative effect on upward earnings management. Since oil price determines companies’ profitability, lower oil price will leads companies to engage in earnings management to achieve higher earnings. Keywords: oil price, earnings management, Indonesian stock exchange. JEL Classifications: M21, M41 DOI: https://doi.org/10.32479/ijeep.9431